2018
DOI: 10.1101/379388
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromulinavorax destructans, a pathogenic TM6 bacterium with an unusual replication strategy targeting protist mitochondrion

Abstract: Most of the diversity of microbial life is not available in culture, and as such we lack even a fundamental understanding of the biological diversity of several branches on the tree of life. One branch that is highly underrepresented is the candidate phylum TM6, also known as the Dependentiae. Their biology is known only from reduced genomes recovered from metagenomes around the world and two isolates infecting amoebae, all suggest that they live highly hostassociated lifestyles as parasites or symbionts. Chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…Bacteria growing in high densities may form biofilms that are typically more tolerant to antimicrobial agents (41) and may result in cytotoxic effects on protist grazers (22). Other bacteria found within aquatic environments have also been shown to lyse protists (10,20,21,42). Our results generally agree with the findings in these reports that lysis occurs within 3 -4 days of co-cultivation with pathogenic bacteria.…”
Section: Virulent Bacteria Display Selective and Density Dependent Ly...supporting
confidence: 90%
See 1 more Smart Citation
“…Bacteria growing in high densities may form biofilms that are typically more tolerant to antimicrobial agents (41) and may result in cytotoxic effects on protist grazers (22). Other bacteria found within aquatic environments have also been shown to lyse protists (10,20,21,42). Our results generally agree with the findings in these reports that lysis occurs within 3 -4 days of co-cultivation with pathogenic bacteria.…”
Section: Virulent Bacteria Display Selective and Density Dependent Ly...supporting
confidence: 90%
“…Our results generally agree with the findings in these reports that lysis occurs within 3 -4 days of co-cultivation with pathogenic bacteria. Similarly to strain-specific grazing of protists (43), predatory bacteria too may display strain-specific lysis of protists (9,42).…”
Section: Virulent Bacteria Display Selective and Density Dependent Ly...mentioning
confidence: 99%
“…Also showing significant abundance increase in zone H was bacterium TM6, a recently nominated pathogen due to the lack of diverse metabolic genes, suggesting a reliance on host by-products (Yeoh et al 2016 ). In a recent study, bacterivorous flagellate Spumella elongate and other protists were shown to be a target species for candidate phyla TM6 bacteria, where cells were infected and lysed (Deeg et al 2018 ). Similarly, filamentous, host reliant and DNA recycling (Starr 2018 ), Saccharibacteria spp (TM7) were highest in zones H. Such interactions may have an impact on the long term structuring of bacteria community composition, especially where distinctive microbes possess capabilities to adapt to change and out-compete more vulnerable species (Matz and Kjelleberg 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the nature of most endosymbiotic interactions remains elusive. The intracellular niches that are occupied by endosymbionts are manifold; some examples include the nucleus , the perinuclear space , the endoplasmic reticulum (Vogt, 1992), chloroplasts (Wilcox, 1986) and mitochondria (Sassera et al, 2006;Deeg et al, 2018). In particular, the latter two are great examples for the Matryoshka doll principle, as symbionts acquired relatively recently replicate inside symbionts acquired hundreds of millions of years ago (Fig.…”
mentioning
confidence: 99%